Periferia Paulistana da necessidade de inserção das habitações de interesse social na Malha Urbana - Omstein, Sheila Walbe (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1990)
This article presents a Post-Occupancy Evaluation (POE) research applied to self-built low-income settlèments located in a Western São Paulo’s city suburb, during the period 1985-1988. It emphasizes the need of a broader evaluation, particulary faced to public spaces, urban infra-structure and low-income districts as a whole, in order to find out ways to include this islands of poverty into the urban context